Análisis del sector hotelero del cantón Montalvo en tiempo de covid-19 - Suconota Moreno, Ana Lucia (2021)
This case study analyzes the situation of the hotel sector in the Montalvo municipality. From one moment to another, this sector faced a totally different situation due to the health emergency that not only affected socially, but also hit the economic sector hard. Montalvo enjoys a wonderful climate and landscape, its geographical location helps tourists visit the same place, both in the coastal region and in the mountains, but as a result of the start of the pandemic, it has been reduced drastically the influx of tourists who came every weekend to enjoy this beautiful area. This research also aims to provide post-covid-19 recommendations for the hotel sector that contributes to the reactivation of tourism. The methodology applied in this research is: exploratory, inductive, and analytical with a qualitative and quantitative approach, to obtain clearer and more precise answers we used the survey that for pandemic reasons was carried out online to the different citizens of the canton.